ASSESSING SELF-REGULATED LEARNING IN PRIMARY SCHOOL: A SYSTEMATIC LITERATURE REVIEW - Dea Fikri Leila Qadaristin (OPTIMA: Journal Of Guidance and Counseling, 2021)
Self-regulated learning needs to be instilled in elementary school-age children because it can help students discover new experiences by seeking information and actively learning independently. Students who organize themselves are theoretically more aware of the task's demands, can accurately predict whether they can meet these demands, are more efficient at learning, relate results to aspects of learning under their control, and have a list of the learning strategies they use appropriately. In a variety of learning situations. The growing interest in research on self-regulated learning has led to self-regulated learning measures, especially in elementary schools, which researchers rarely do. The method in this study uses systematic literature review by identifying instruments that measure self-regulated learning. Steps are taken through several stages of identifying and filtering articles with predetermined criteria. The results of thisstudy will obtain an overview of the distribution of instruments used in elementary schools as a consideration in measuring the self-regulated learning of elementary school students effectively.